Electrolyte, secondary battery and electric device

By using a non-aqueous solvent containing the compound of formula I in the lithium battery electrolyte, the problem of degradation of lithium battery performance in a low temperature environment is solved, and the high ionic conductivity and stable SEI film formation of the electrolyte are achieved, which improves the low temperature performance and cycle stability of the battery.

CN119627237AActive Publication Date: 2025-03-14SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411786203.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-14
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

Lithium batteries show problems such as reduced charging and discharging capacity, increased internal resistance, and shortened battery life in low-temperature environments with temperatures below -20℃, which limits their use in aerospace, military and polar exploration.

Method used

An electrolyte solution is provided, including a non-aqueous solvent, a lithium salt and an additive. The non-aqueous solvent contains a compound of the structure shown in Formula I. The compound can effectively separate the lithium salt in the electrolyte under low temperature conditions, form a solvated structure, promote the transmission of lithium ions, and form a stable SEI film on the surface of the negative electrode.

Benefits of technology

Under low temperature conditions, the ionic conductivity of the electrolyte increases, the transmission efficiency of lithium ions is improved, forming a stable SEI film, extending the cycle life of the battery and improving capacity retention.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627237A_ABST
    Figure CN119627237A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte, a secondary battery and an electric device, and belongs to the technical field of secondary batteries. The non-aqueous solvent contained in the electrolyte can be based on diamide groups contained in a special structure of the non-aqueous solvent, lithium salt in the electrolyte can be effectively separated under the low-temperature condition, a solvation structure can be formed easily, transmission of lithium ions is promoted, and the ionic conductivity in the electrolyte is improved; meanwhile, the reduction potential of the non-aqueous solvent is high, and the non-aqueous solvent is not decomposed in the charging and discharging processes of the battery, so that the lithium salt can be stably dissolved, and the impedance of the battery in the charging and discharging processes is reduced; the additive with low reduction potential preferentially reacts with the non-aqueous solvent with high reduction positioning, a stable SEI layer is formed on the surface of the negative electrode, decomposition of the non-aqueous solvent is reduced, in addition, a small amount of decomposed non-aqueous solvent and the decomposed additive form a stable SEI film, a uniform and stable protection layer is formed, and the capacity retention rate of the battery in the circulation process is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to an electrolyte, a secondary battery and an electrical device. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, aerospace, and outdoor equipment due to their high energy density and long cycle life. However, lithium batteries show problems such as decreased charge and discharge capacity, increased internal resistance, and shortened battery life in low-temperature environments below -20°C, which limits the use of lithium batteries in some aerospace, military, and polar exploration fields, as well as in high-altitude and high-latitude areas.

[0003] Under low temperature conditions, the performance of lithium batteries will decline significantly, which is mainly reflected in the following aspects: First, the viscosity of the electrolyte increases as the temperature decreases, the ionic conductivity decreases, and the diffusion rate of lithium ions slows down; second, the solid electrolyte interface film (SEI film) on the surface of the negative electrode cannot be effectively formed or stabilized at low temperatures, which hinders the transmission of lithium ions between the electrolyte and the negative electrode; third, lithium deposition caused by excessive polarization may also bring safety hazards, such as the formation of lithium dendrites, increasing the risk of short circuits; fourth, low temperatures will also aggravate the decomposition of lithium salts (such as LiPF6), resulting in unstable electrolyte components.

[0004] Therefore, how to improve the performance of lithium batteries in a low temperature environment below -20°C has become a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention

[0005] The purpose of the present disclosure is to overcome the deficiencies of the prior art and to provide an electrolyte, a secondary battery and an electrical device. The electrolyte can effectively separate lithium salts in the electrolyte under low temperature conditions, which is conducive to the formation of a solvation structure, promotes the transmission of lithium ions, improves the ionic conductivity in the electrolyte, and forms a stable SEI film, thereby improving the performance of the battery under low temperature conditions.

[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present disclosure is as follows: In the first aspect of the present application, the present application provides an electrolyte, including a non-aqueous solvent, a lithium salt and an additive, wherein the non-aqueous solvent includes at least one of the compounds of the structure shown in Formula I:

[0007]

[0008] Wherein, R1 and R2 are each independently selected from at least one of a cyano group, a sulfonic acid group, a C1-C5 perfluoroalkyl group, an imidazole group, an alkynyl group, an alkenyl group, an ether group, a carboxyl group, an isocyanate group and an ester group.

[0009] As a preferred embodiment of the present application, the non-aqueous solvent includes at least one of the compounds shown in the following structures:

[0010]

[0011] As a preferred embodiment of the present application, based on the total mass of the electrolyte, the mass percentage of the compound having the structure shown in formula I is 10-40%.

[0012] As a preferred embodiment of the present application, the mass ratio of the compound having the structure shown in Formula I to the additive is 3-14.

[0013] As a preferred embodiment of the present application, the additive is at least one of fluoroethylene carbonate, ethylene glycol dimethyl ether, trifluorophosphate, vinylene carbonate, 1,3-propane sultone and methyl methacrylate.

[0014] As a preferred embodiment of the present application, the non-aqueous solvent further comprises an ester solvent, and the mass ratio of the compound having the structure represented by Formula I to the ester solvent is 0.1-1.

[0015] As a preferred embodiment of the present application, the ester solvent is a carbonate solvent, and the carbonate solvent includes at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl propyl carbonate, methyl ethyl carbonate, and methyl butyl carbonate.

[0016] As a preferred embodiment of the present application, the mass ratio of the compound having the structure shown in Formula I to the lithium salt is 0.6-3.

[0017] In a second aspect of the present application, the present application provides a secondary battery, comprising a positive electrode, a negative electrode, a separator and the electrolyte.

[0018] In a third aspect of the present application, the present application provides an electrical device, comprising the secondary battery.

[0019] The beneficial effects of the present application are as follows: the non-aqueous solvent of the structure shown in Formula I of the present application contains a diamide group in its molecular structure, and the diamide group has high polarity, so that the non-aqueous solvent of the structure shown in Formula I can effectively separate the lithium salt in the electrolyte under low temperature conditions, which is conducive to the formation of a solvation structure, promotes the transmission of lithium ions, and improves the ionic conductivity in the electrolyte; secondly, the reduction potential of the non-aqueous solvent of the structure shown in Formula I is relatively high, which can ensure that it is not decomposed during the charging and discharging process of the battery, thereby being able to stably dissolve the lithium salt and reduce the impedance of the battery during the charging and discharging process; thirdly, the reduction potential of the additive is relatively low, and during the charging and discharging process, the non-aqueous solvent of the structure shown in Formula I is preferentially reduced to form a stable SEI layer on the surface of the negative electrode, reducing the decomposition of the non-aqueous solvent of the structure shown in Formula I, and at the same time, a small amount of decomposed non-aqueous solvent of the structure shown in Formula I forms a stable SEI film with the decomposed additive, forming a uniform and stable protective layer, thereby improving the capacity retention rate of the battery during the cycle process. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a Raman spectrum of the compound of structural formula A1;

[0021] Figure 2 is a Raman spectrum of the compound of structural formula A2;

[0022] Figure 3 is a Raman spectrum of the compound of structural formula A3;

[0023] Figure 4 is a Raman spectrum of the compound of structural formula A4;

[0024] Figure 5 is a Raman spectrum of the compound of structural formula A5;

[0025] Figure 6 is a Raman spectrum of the compound of structural formula A6;

[0026] Figure 7 is a Raman spectrum of the compound of structural formula A7;

[0027] Figure 8 is a Raman spectrum of the compound of structural formula A8;

[0028] Fig. 9 is a Raman spectrum of the compound of structural formula A9;

[0029] Fig.10 It is the Raman spectrum of the compound of structural formula A10. DETAILED DESCRIPTION

[0030] In order to facilitate understanding of the present disclosure, the present disclosure will be described more fully below. However, the present disclosure can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present disclosure more thorough and comprehensive.

[0031] As used herein:

[0032] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0033] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0034] When amount, concentration or other value or parameter is represented by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1-5", described range should be interpreted as including range "1-4", "1-3", "1-2", "1-2 and 4-5", "1-3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.

[0035] In these examples, parts and percentages are by mass unless otherwise indicated.

[0036] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0037] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0038] In order to solve the problem that the performance of lithium batteries in the prior art is significantly reduced in a low temperature environment below -20°C.

[0039] The embodiment of the present application provides an electrolyte, including a non-aqueous solvent, a lithium salt and an additive, wherein the non-aqueous solvent includes at least one of the compounds of the structure shown in Formula I:

[0040]

[0041] Wherein, R1 and R2 are each independently selected from at least one of a cyano group, a sulfonic acid group, a C1-C5 perfluoroalkyl group, an imidazole group, an alkynyl group, an alkenyl group, an ether group, a carboxyl group, an isocyanate group and an ester group.

[0042] The non-aqueous solvent of the structure shown in Formula I of the present application contains a diamide group in its molecular structure. The diamide group has a high polarity, so that the non-aqueous solvent of the structure shown in Formula I can effectively separate the lithium salt in the electrolyte under low temperature conditions, which is conducive to the formation of a solvation structure, promotes the transmission of lithium ions, and improves the ionic conductivity in the electrolyte; secondly, the reduction potential of the non-aqueous solvent of the structure shown in Formula I is relatively high, which can ensure that it is not decomposed during the charging and discharging process of the battery, thereby being able to stably dissolve the lithium salt and reduce the impedance of the battery during the charging and discharging process; thirdly, the reduction potential of the additive is relatively low. During the charging and discharging process, the non-aqueous solvent of the structure shown in Formula I is preferentially reduced to form a stable SEI layer on the surface of the negative electrode, reducing the decomposition of the non-aqueous solvent of the structure shown in Formula I. At the same time, a small amount of decomposed non-aqueous solvent of the structure shown in Formula I forms a stable SEI film with the decomposed additive, forming a uniform and stable protective layer, thereby improving the capacity retention rate of the battery during the cycle process.

[0043] Exemplarily, the method for preparing the compound of the structure shown in Formula I comprises the following steps:

[0044] In the presence of a first catalyst, oxalyl diamine and a compound containing an R1 functional group undergo a first reaction to obtain a first compound substituted with an R1 functional group;

[0045] The first compound substituted with the R1 functional group is subjected to a second reaction with the compound containing the R2 functional group, a pH adjuster is added for neutralization, and the mixture is filtered to obtain a compound with a structure shown in Formula I.

[0046] Exemplarily, the solvent includes dichloromethane, dichloroethane, THF, and the amount of the solvent added is not particularly limited.

[0047] Exemplarily, the molar ratio of oxalyl diamide to the compound containing the R1 functional group is 1:1-1.1.

[0048] Exemplarily, the molar ratio of the first compound substituted with the R1 functional group to the compound containing the R2 functional group is 1:1.5-2.

[0049] Exemplarily, the first catalyst is tetrabutylammonium bromide (TBAB);

[0050] Exemplarily, the temperature of the first reaction is 20-30°C.

[0051] Exemplarily, the temperature of the second reaction is not specifically limited and is selected according to the different compounds containing the R2 functional group. For example, when the R2 functional group is a carboxyl group, a sulfonic acid group or an acyl group, the reaction temperature is 0-5°C, and when the R2 functional group is a cyano group, the reaction temperature is 20-30°C.

[0052] Exemplarily, the raw materials for the second reaction also include an activator or a second catalyst. The type of the activator or catalyst is not specifically limited and is selected according to the R2 functional group. For example, when the R2 functional group is a carboxyl group or a sulfonic acid group, the activator is thionyl chloride; for example, when the R2 functional group is an olefin group or a phenyl group, the second catalyst is an alkaline catalyst such as potassium carbonate.

[0053] Exemplarily, the reaction equation of the compound of the structure shown in Formula I is as follows:

[0054]

[0055] Wherein, X1 is a compound containing an R1 functional group, and X2 is a compound containing an R2 functional group.

[0056] In one embodiment, the compound containing the R1 functional group includes at least one of pentafluoroethyl iodide, pyrazole, acetic acid, hexafluoroethylene, ethylene oxide, bromobenzene, methyl bromide, and ethyl bromide.

[0057] In one embodiment, the compound containing the R2 functional group includes at least one of chlorosulfonic acid, sodium cyanide, methanol, bromobenzene, oxalyl chloride, formyl chloride, acetyl chloride, and vinyl bromide.

[0058] In one embodiment, the non-aqueous solvent comprises at least one of the compounds shown below:

[0059]

[0060] When the compound of the above structure is selected as the non-aqueous solvent, due to the further optimization effect of the groups contained in the structure, the performance of the obtained electrolyte is better, and the product can achieve higher low-temperature performance when used in secondary batteries.

[0061] The details are as follows: Non-aqueous solvents A1, A4, A5, and A10 all have a long chain structure. Under low temperature conditions, the chain structure can change the molecular structure and the interaction between atoms. This effect helps to improve the fluidity of the electrolyte under low temperature conditions, so that lithium ions can have sufficient migration ability under low temperature conditions. Non-aqueous solvents A7 and A9 have shorter chain lengths, and their effect on improving the diffusion ability of lithium ions under low temperature is slightly inferior to that of non-aqueous solvents A1, A4, A5, and A10.

[0062] The fluorine-containing functional group and sulfate functional group in the compound of the structure shown in Formula I can reduce the freezing point and viscosity of the electrolyte, thereby maintaining the fluidity of the electrolyte under low temperature conditions and ensuring good migration of lithium ions at low temperatures.

[0063] The ether group in the compound of the structure shown in Formula I can reduce the viscosity of the electrolyte on the one hand, and on the other hand, it has polar characteristics, which increases the solubility of lithium salt in the electrolyte, helps to improve the separation ability between lithium ions and anions, and improves the ionic conductivity of lithium ions.

[0064] The unsaturated bonds in the compound of the structure shown in Formula I reduce the rotational freedom of the molecule to a certain extent, which will affect the viscosity of the electrolyte, but it helps the cross-linking reaction to form a denser SEI film on the negative electrode surface, thereby improving the overall stability of the battery.

[0065] The non-aqueous solvents A2, A3, and A6 contain a ring structure, which affects the viscosity of the electrolyte to a certain extent.

[0066] In one embodiment, based on the total mass of the electrolyte, the mass percentage of the compound of the structure shown in Formula I is 10-40%, for example, it can be but not limited to 10%, 12%, 15%, 17%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, 38%, 40%.

[0067] In one embodiment, based on the total mass of the electrolyte, the mass percentage of the compound of the structure shown in Formula I is 15-40%, for example, it can be but not limited to 15%, 15.5%, 17%, 17.5%, 20%, 23%, 25%, 28%, 30%, 35.5%, 40%. The compound of the structure shown in Formula I has high polarity and can enhance the solubility of the electrolyte under low temperature conditions, thereby promoting the transmission efficiency of lithium ions. If the content of the compound of the structure shown in Formula I is too high, the SEI film formed will be too thick or uneven, which not only reduces the stability of the negative electrode, but also increases the difficulty of lithium ions passing through; the low temperature performance of the secondary battery is reduced.

[0068] In one embodiment, based on the total mass of the electrolyte, the mass percentage of the compound of the structure shown in Formula I is 15-30%, for example, it can be but not limited to 15%, 15.5%, 17%, 17.5%, 20%, 23%, 25%, 28%, 30%.

[0069] In one embodiment, the mass ratio of the compound of the structure represented by Formula I to the additive is 3-14, for example, but not limited to 3, 3.33, 4, 5, 5.5, 6, 6.67, 8, 10, 12, 13.33, 14.

[0070] In one embodiment, the additive is at least one of fluoroethylene carbonate (FEC), ethylene glycol dimethyl ether (DME), trifluorophosphate (TFP), vinylene carbonate (VC), 1,3-propane sultone (PS) and methyl methacrylate (MMA).

[0071] Preferably, the additive is fluoroethylene carbonate.

[0072] Under low temperature conditions, fluoroethylene carbonate is conducive to forming a stable SEI film on the negative electrode, while the compound with the structure shown in Formula I can improve the fluidity of the electrolyte under low temperature conditions and ensure the transmission efficiency of lithium ions; the two complement each other, while improving the battery capacity retention rate, they also reduce the impedance in the battery. However, if the ratio between the two is excessive, the SEI film formed on the negative electrode surface will be uneven, thereby reducing the capacity retention rate of the secondary battery.

[0073] Exemplarily, in the present application, the additive accounts for 0.1-6% of the total mass of the electrolyte, for example, it can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0074] Under low temperature conditions, fluoroethylene carbonate can effectively help the electrolyte form a stable SEI film on the surface of the negative electrode and prevent the decomposition of EC. However, if the mass percentage of fluoroethylene carbonate is too high, it will first cause the SEI formed to be too thick, thereby increasing the difficulty of lithium ions entering the negative electrode. In addition, too much fluoroethylene carbonate will also cause more HF to be generated in the electrolyte, thereby corroding the positive electrode.

[0075] In one embodiment, the non-aqueous solvent also includes an ester solvent, and the mass ratio of the compound of the structure represented by Formula I to the ester solvent is 0.1-1, for example, it can be but not limited to 0.1, 0.14, 0.22, 0.32, 0.34, 0.37, 0.4, 0.57, 0.94, 1.

[0076] Taking the ester solvent of a mixture of ethylene carbonate, propylene carbonate and diethyl carbonate as an example, the polarity of the diamide group in the compound of the structure shown in Formula I and the high dielectric constant EC can effectively dissolve lithium salts and separate lithium ions and anions, effectively improving the solubility of lithium salts in the electrolyte; the mixture of PC and DEC helps the diffusion of lithium ions under low temperature conditions and forms a SEI film, thereby reducing battery impedance and improving the battery capacity retention rate.

[0077] In one embodiment, the non-aqueous solvent also includes an ester solvent, and the mass ratio of the compound of the structure represented by Formula I to the ester solvent is 0.15-0.6, for example, it can be but not limited to 0.15, 0.22, 0.32, 0.34, 0.37, 0.4, 0.57, 0.6.

[0078] In one embodiment, the ester solvent is a carbonate solvent, and the carbonate solvent includes at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), methyl propyl carbonate (MPC), methyl ethyl carbonate (MEC), and methyl butyl carbonate (MBIC).

[0079] Preferably, the carbonate solvent is a mixture of ethylene carbonate, propylene carbonate and diethyl carbonate, and the mass ratio of the ethylene carbonate, propylene carbonate and diethyl carbonate is 1:1:1-1:1:3.

[0080] Diethyl carbonate has a low viscosity, which is beneficial to improving the transmission capacity of lithium ions in the electrolyte. However, due to the low dielectric constant of ethylene carbonate, if the content of diethyl carbonate is further increased, the solubility of the electrolyte will be reduced, and the lithium ions and anions in the lithium salt cannot be effectively separated, resulting in a decrease in the transmission capacity of lithium ions. In addition, too much ethylene carbonate causes the viscosity of the electrolyte to be too low, making it difficult to form the SEI film, affecting the stability of the battery's negative electrode, thereby reducing the capacity retention rate.

[0081] In one embodiment, the content of the ester solvent is greater than 30% based on the total mass of the electrolyte.

[0082] In one embodiment, the content of the fluoroethylene carbonate and the compound of formula I is greater than 12% based on the total mass of the electrolyte.

[0083] In one embodiment, based on the total mass of the electrolyte, the content of the fluoroethylene carbonate and the compound of formula I is less than 40%.

[0084] In one embodiment, based on the total mass of the electrolyte, the content of the fluoroethylene carbonate and the compound A1 of the formula I is greater than 10%.

[0085] In one embodiment, based on the total mass of the electrolyte, the content of the fluoroethylene carbonate and the compound A1 of the formula I is less than 45%.

[0086] In one embodiment, the mass ratio of the compound of the structure represented by Formula I to the lithium salt is 0.6-3, for example, it can be but not limited to 0.6, 0.9, 1.2, 1.5, 1.8, 2.1, 2.4, 2.7, 3.

[0087] Since the diamide group in the compound of the structure shown in Formula I has a high polarity, it can effectively separate the lithium ions and anions in the electrolyte, thereby effectively improving the transmission capacity of lithium ions in the electrolyte. However, too much lithium salt will lead to the formation of a large number of ion pairs or ion clusters, which will hinder the transmission of lithium ions.

[0088] In one embodiment, the lithium salt includes at least one of MClO4, MBF4, MPF6, MAsF6, MBOB, MFSI, MTFSI, MPF2O2, MCF3SO3, MCF3SO3, and MPF2(C2O4), wherein M is Li, Na, or K.

[0089] In one embodiment, the lithium salt includes at least one of LiPF6, LiPF2(C2O4) and LiFSI.

[0090] Exemplarily, in the present application, the lithium salt accounts for 5-20% of the total mass of the electrolyte, for example, it can be 5%, 8%, 10%, 12%, 13%, 15%, 18%, 20%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0091] A lithium salt with too little mass percentage will reduce the number of lithium ions available for conduction in the electrolyte, resulting in very low conductivity. On the other hand, a lithium salt with too much mass percentage will increase the viscosity of the electrolyte and form too many ion pairs or ion clusters in the electrolyte, both of which will reduce the transmission capacity of lithium ions in the electrolyte. Only an appropriate amount of lithium salt can ensure that the electrolyte can become an effective part of the battery charging and discharging process.

[0092] It should be noted that the present application does not specifically limit the method for preparing the electrolyte, and those skilled in the art can prepare it into an electrolyte according to conventional technical means, for example, by uniformly mixing an organic solvent, a lithium salt, and an additive.

[0093] In one embodiment of the present application, the present application provides a secondary battery, including a positive electrode, a negative electrode, a separator and the electrolyte.

[0094] Exemplarily, the positive electrode comprises a positive electrode active material capable of extracting and inserting lithium ions, and the negative electrode comprises a negative electrode active material capable of inserting and extracting lithium ions.

[0095] Specifically, the positive electrode active material is a lithium-containing composite oxide. Specific examples of lithium-containing composite oxides include LiMnO2, LiFeO2, LiMn2O4, Li2FeSiO4, LiNi5CO2Mn3O2, Li z Ni (1-x-y) Co x M y O2 (x, y and z are values ​​satisfying 0.01≤x≤0.20, 0≤y≤0.20 and 0.97≤z≤1.20, and M represents at least one element selected from Mn, V, Mg, B and Al), LiFePO4 and Li z CO (1-x) M x At least one of O2 (x and z are values ​​satisfying 0≤x≤0.1 and 0.97≤z≤1.20, and M represents at least one element selected from the group consisting of Mn, V, Mg, B and Al). However, the present application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries can also be used. These positive electrode active materials can be used alone or in combination of two or more.

[0096] Specifically, the negative electrode active material can be selected from graphite materials, silicon-based materials, metal oxides, metal sulfides, metal materials, etc. The graphite material can be selected from at least one of artificial graphite, natural graphite, soft carbon, and hard carbon. The silicon-based material can be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The metal oxide can be selected from at least one of tin oxide, zinc oxide, and vanadium dioxide. The metal sulfide can be selected from at least one of tin sulfide, molybdenum sulfide, and zinc sulfide. The alloy material can be selected from at least one of tin, aluminum, gallium, germanium, lithium, and lithium silicon alloy. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.

[0097] In the secondary battery mentioned in the present application, the specific type of the isolation membrane is not subject to specific restrictions, and can be any isolation membrane material used in existing batteries, such as polyethylene, polypropylene, polyvinylidene fluoride and their multilayer composite membranes, but not limited to these.

[0098] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0099] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0100] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.

[0101] Exemplarily, in the secondary battery of the present application, the battery's charge cut-off voltage may be no less than 4.2 V, that is, the battery may be used in a high voltage state of no less than 4.2 V. Preferably, the battery may operate in the range of 4.2 V-4.9 V, and further preferably, the battery may operate in the range of 4.3 V-4.8 V.

[0102] In one embodiment of the present application, the present application provides an electrical device including the secondary battery.

[0103] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0104] In a specific embodiment of the present invention, the preparation method of the compound of structural formula A1 is:

[0105] S1: at room temperature, tetrabutylammonium bromide TBAB (1.0 g) was added to a mixed solution of oxalyl diamine (0.1 mol) and pentafluoroethyl iodide (0.1 mol) in dichloromethane (50 mL), and the mixture was stirred for 6 h to obtain a first compound solution;

[0106] S2: The first compound solution obtained in step S1 was cooled to 3°C, chlorosulfonic acid (0.1 mol) and thionyl chloride (20 mL) were added, and the reaction was stirred for 6 hours to obtain a second compound solution, saturated sodium bicarbonate was added until the pH of the second compound solution was 7, and then extraction, washing, and recrystallization were performed in sequence to obtain a compound of structural formula A1; the Raman spectrum of the compound of structural formula A1 is as follows: Figure 1 shown.

[0107] In a specific embodiment of the present invention, the preparation method of the compound of structural formula A2 is:

[0108] S1: At room temperature, tetrabutylammonium bromide (0.3 g) was added to a mixed solution of oxalyl diamine (0.1 mol) and pyrazole (0.1 mol) in dichloromethane (50 mL), and the mixture was stirred for 6 h to obtain a first compound solution;

[0109] S2: Sodium cyanide (0.15 mol) was added to the first compound solution obtained in step S1, and the mixture was stirred for 6 hours to obtain a second compound solution. Acetic acid was added until the pH of the second compound solution was 7, and then the mixture was extracted, washed, and recrystallized to obtain a compound of structural formula A2. The Raman spectrum of the compound of structural formula A2 is shown in FIG. Figure 2 shown.

[0110] In a specific embodiment of the present invention, the preparation method of the compound of structural formula A4 is:

[0111] S1: At room temperature, thionyl chloride (20 mL) was added to a mixed solution of oxalyl diamine (0.1 mol) and acetic acid (0.1 mol) in dichloromethane (50 mL), and the mixture was stirred for 12 h to obtain a first compound solution;

[0112] S2: Methanol (0.1 mol), methyl chloride (0.1 mol) and hydrogen chloride were added to the first compound solution obtained in step S1, and the mixture was stirred and reacted for 6 hours under heating reflux to obtain a second compound solution, saturated sodium bicarbonate was added until the pH of the second compound solution was 7, and then extraction, washing and recrystallization were performed in sequence to obtain a compound of structural formula A4; the Raman spectrum of the compound of structural formula A4 is as follows: Figure 4 shown.

[0113] In a specific embodiment of the present invention, the preparation method of the compound of structural formula A5 is:

[0114] S1: at room temperature, tetrabutylammonium bromide TBAB (1 g) was added to a mixed solution of oxalyl diamine (0.1 mol) and hexafluoroethylene (0.1 mol) in dichloromethane (50 mL), and the mixture was stirred for 6 h to obtain a first compound solution;

[0115] S2: Sodium cyanide (0.15 mol) was added to the first compound solution obtained in step S1, and the mixture was stirred for 6 hours to obtain a second compound solution. Acetic acid was added until the pH of the second compound solution was 7, and then the mixture was extracted, washed, and recrystallized to obtain a compound of formula A5. The Raman spectrum of the compound of formula A5 is shown in FIG. Figure 2 shown.

[0116] In a specific embodiment of the present invention, the preparation method of the compound of structural formula A6 is:

[0117] S1: at room temperature, tetrabutylammonium bromide TBAB (0.2 g) was added to a mixed solution of oxalyl diamine (0.1 mol) and pyrazole (0.1 mol) in dichloromethane (50 mL), and the mixture was stirred for 6 h to obtain a first compound solution;

[0118] S2: Add bromobenzene (0.1 mol) and potassium carbonate (4.2 g) to the first compound solution obtained in step S1, stir and react for 8 h under heating reflux to obtain a second compound solution, add acetic acid until the pH of the second compound solution is 7, and then extract, wash and recrystallize in sequence to obtain a compound of structural formula A6; the Raman spectrum of the compound of structural formula A6 is as follows: Figure 6 shown.

[0119] In a specific embodiment of the present invention, the preparation method of the compound of structural formula A7 is:

[0120] S1: at room temperature, tetrabutylammonium bromide TBAB (0.3 g) was added to a mixed solution of oxalyl diamine (0.1 mol) and ethylene oxide (0.1 mol) in dichloromethane (50 mL), and the mixture was stirred for 12 h to obtain a first compound solution;

[0121] S2: The first compound solution obtained in step S1 was cooled to 3°C, oxalyl chloride (0.1 mol) was added, and the mixture was stirred for 6 hours to obtain a second compound solution. Acetic acid was added until the pH of the second compound solution was 7, and then the mixture was extracted, washed, and recrystallized to obtain a compound of structural formula A7. The Raman spectrum of the compound of structural formula A7 is shown in FIG. Figure 7 shown.

[0122] In a specific embodiment of the present invention, the preparation method of the compound of structural formula A8 is:

[0123] S1: at room temperature, tetrabutylammonium bromide TBAB (0.5 g) was added to a mixed solution of oxalyl diamine (0.1 mol) and bromobenzene (0.1 mol) in dichloromethane (50 mL), and the mixture was stirred for 12 h to obtain a first compound solution;

[0124] S2: The first compound solution obtained in step S1 was cooled to 3°C, and formyl chloride (0.1 mol) was added. After stirring for 6 hours, a second compound solution was obtained. Acetic acid was added until the pH of the second compound solution was 7, and then the solution was extracted, washed, and recrystallized to obtain a compound of structural formula A8. The Raman spectrum of the compound of structural formula A8 is as follows: Figure 8 shown.

[0125] In a specific embodiment of the present invention, the preparation method of the compound of structural formula A9 is:

[0126] S1: at room temperature, tetrabutylammonium bromide TBAB (1 g) was added to a mixed solution of oxalyl diamine (0.1 mol) and methyl bromide (0.1 mol) in dichloromethane (50 mL), and the mixture was stirred for 12 h to obtain a first compound solution;

[0127] S2: The first compound solution obtained in step S1 was cooled to 3°C, acetyl chloride (0.1 mol) was added, and the mixture was stirred for 6 hours to obtain a second compound solution. Acetic acid was added until the pH of the second compound solution was 7, and then the mixture was extracted, washed, and recrystallized to obtain a compound of structural formula A9. The Raman spectrum of the compound of structural formula A9 is shown in FIG. Fig. 9 shown.

[0128] In a specific embodiment of the present invention, the preparation method of the compound of structural formula A10 is:

[0129] S1: at room temperature, tetrabutylammonium bromide TBAB (0.3 g) was added to a mixed solution of dichloromethane (50 mL) containing oxalyl diamine (0.1 mol) and ethyl bromide (0.1 mol), and the mixture was stirred for 12 h to obtain a first compound solution;

[0130] S2: The first compound solution obtained in step S1 was cooled to 3°C, vinyl bromide (0.1 mol) was added, and the reaction was stirred for 10 hours to obtain a second compound solution, acetic acid was added until the pH of the second compound solution was 7, and then extraction, washing, and recrystallization were performed in sequence to obtain a compound of structural formula A10; the Raman spectrum of the compound of structural formula A10 is as follows Fig.10 shown.

[0131] It should also be noted that the preparation method of the compounds described in structural formula A1-A10 of the present invention is not limited thereto, and those skilled in the art should be aware that the same products prepared by other synthetic methods are also applicable to the scheme of the present invention.

[0132] The present invention is further described below with specific embodiments:

[0133] Example 1

[0134] The method for preparing the electrolyte comprises the following steps:

[0135] At room temperature, in a glove box filled with argon (H2O<1ppm, O2<1ppm), EC (ethylene carbonate), PC (propylene carbonate) and DEC (diethyl carbonate) were mixed at a mass ratio of 1:1:1 to obtain a first solvent, and then the compound of structural formula A1 was added and mixed evenly. The molecular sieve removes water to obtain a second solvent;

[0136] Fluoroethylene carbonate (FEC) and lithium difluorobis(oxalate) phosphate (LiPF2(C2O4)) are added to the second solvent and mixed evenly to obtain a mixed solution, and then lithium hexafluorophosphate (LiPF6) is added to the mixed solution and stirred evenly to obtain an electrolyte.

[0137] The electrolyte includes the following components in percentage by mass: 3% FEC, 5% compound of structural formula A1, 13% LiPF6, 1.5% LiPF2(C2O4), and 77.5% first solvent (ester solvent).

[0138] Preparation of secondary batteries:

[0139] (1) The positive electrode active material lithium nickel cobalt manganese oxide (NCM811), the conductive agent acetylene black (Super P) and the binder polyvinylidene fluoride (PVDF) are mixed uniformly in a mass ratio of NCM811:Super P:PVDF=8:1:1, and uniformly dispersed in N-methylpyrrolidone (NMP) to prepare a uniform black slurry, and the mixed black slurry is coated on both sides of an aluminum foil, and then baked, rolled and cut into pieces to obtain a positive electrode sheet;

[0140] (2) The negative electrode active material silicon oxide-carbon material, the conductive agent acetylene black (Super P) and the binder SBR are mixed uniformly in a mass ratio of graphite:Super P:SBR=9:0.5:0.5, and evenly dispersed in deionized water to form a uniform black slurry. The mixed slurry is coated on both sides of the copper foil, and then baked, rolled and cut into pieces to obtain the negative electrode sheet;

[0141] (3) The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, with the separator being located between the positive and negative electrode sheets. After winding, hot pressing and shaping, and tab welding, a 2Ah bare cell is obtained. The bare cell is placed in an outer packaging aluminum-plastic film and baked in an oven at 85±10°C for 24 hours. 10 g of the electrolyte obtained in each embodiment is injected into the dried battery, and the battery is allowed to stand at 45°C for 24 hours, formed, and divided to complete the preparation of a lithium-ion secondary soft-pack battery.

[0142] Examples 2-19, Comparative Examples 1-3

[0143] The differences between Examples 2-19, Comparative Examples 1-3 and Example 1 are shown in Table 1, and the rest are the same as Example 1.

[0144] Embodiment 20

[0145] The difference between Example 20 and Example 1 is that the content of lithium hexafluorophosphate is adjusted to 15%.

[0146] Test Case

[0147] Battery performance test

[0148] (1) Low temperature impedance test:

[0149] The soft-pack batteries obtained in the embodiment and the comparative example were left to stand at 0°C, -20°C and -40°C for 1 hour respectively to ensure uniform temperature distribution and stability; then, the impedance of the batteries was tested at 0°C, -20°C and -40°C under the conditions of an AC signal with a frequency range of 100kHz to 0.01Hz and an applied voltage disturbance amplitude of 5-10mV.

[0150] (2) Low temperature storage performance test: At -40°C, the prepared battery was charged to 4.5V at a constant current of 0.5C, and then charged at a constant voltage of 4.5V (the cut-off current was 0.01C); then discharged at a constant current of 0.5C to 3.0V, and the discharge capacity was recorded as the initial discharge capacity. Charged to 4.5V at a constant current of 0.5C, and then charged at a constant voltage of 4.5V (the cut-off current was 0.01C), the battery was placed in a -40°C constant temperature box for 10 days, and then discharged to 3.0V at a constant current of 0.5C at -40°C, and the discharge capacity was recorded as the retention capacity. Then, at -40°C, the battery was charged and discharged once at the same 0.5C cycle, and the discharge capacity was recorded as the recovery capacity. The high temperature storage performance of the battery was calculated as follows: Battery capacity retention rate = retention capacity / initial capacity × 100%; Battery capacity recovery rate = recovery capacity / initial capacity × 100%.

[0151] The test results are shown in Table 1.

[0152] Table 1

[0153]

[0154]

[0155] Table 2 Performance test data of embodiments and comparative examples

[0156]

[0157] From Examples 1-20, it can be seen that the capacity retention rate of the battery obtained by using the electrolyte of the present application is greater than 31%, and can reach up to 44.13%; the capacity recovery rate is greater than 61%, and can reach up to 73.21%. This shows that the compound of the structure shown in Formula I of the present application can effectively separate the lithium salt in the electrolyte under low temperature conditions, which is conducive to forming a solvated structure, promoting the transmission of lithium ions, and improving the ionic conductivity in the electrolyte. At the same time, the lithium salt is stably dissolved to form a stable SEI film, thereby improving the capacity retention rate and capacity recovery rate of the battery.

[0158] From comparative examples 1-7, it can be seen that when the amount of the compound of the structure shown in formula I is 10-40%, and the mass ratio of the compound of the structure shown in formula I to the additive is 3-14, after the obtained battery is stored in a -40°C constant temperature box for 10 days, the capacity retention rate of the battery is 38.29-44.13%, and the capacity recovery rate is 68.51-73.21%, indicating that when the amount of the compound of the structure shown in formula I is 10-40%, and the mass ratio of the compound of the structure shown in formula I to the additive is 3-14, the combination of the compound of the structure shown in formula I and the additive can further improve the capacity retention rate and capacity recovery rate of the battery under low temperature conditions.

[0159] By comparing Example 4 and Examples 11-13, it can be seen that when the additive is FEC, the capacity retention rate and capacity recovery rate of the battery are better after the obtained battery is stored in a -40°C constant temperature box for 10 days, indicating that the performance of the obtained battery at low temperatures is better when the additive FEC and the compound of the structure shown in Formula I are used in combination.

[0160] By comparing Example 4 and Examples 14-19, it can be seen that when the compound with the structure shown in Formula I is A1, A4, A5, and A10, after the obtained battery is stored in a -40°C constant temperature box for 10 days, the capacity retention rate of the battery is 40.29-44.13%, and the capacity recovery rate is 70.13-73.21%, indicating that when the compound with the structure shown in Formula I is A1, A4, A5, and A10, the capacity retention rate and capacity recovery rate of the battery under low temperature conditions are better.

[0161] By comparing Example 4 with Comparative Examples 1-3, it can be seen that the compound of the structure shown in Formula I of the present application and the additive have a synergistic effect. Under low temperature conditions, the two jointly form a stable SEI film, which effectively improves the capacity retention rate and capacity recovery rate of the battery under low temperature conditions.

[0162] Finally, it should be noted that the above embodiments are used to illustrate the technical solution of the present disclosure rather than to limit the protection scope of the present disclosure. Although the present disclosure has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present disclosure can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present disclosure.

Claims

1. An electrolyte, characterized in that: It includes a non-aqueous solvent, a lithium salt and an additive, wherein the non-aqueous solvent includes at least one of the compounds of the structure shown in Formula I: Wherein, R1 and R2 are each independently selected from at least one of a cyano group, a sulfonic acid group, a C1-C5 perfluoroalkyl group, an imidazole group, an alkynyl group, an alkenyl group, an ether group, a carboxyl group, an isocyanate group and an ester group.

2. The electrolyte according to claim 1, characterized in that The non-aqueous solvent includes at least one of the compounds shown below:

3. The electrolyte according to claim 1, characterized in that Based on the total mass of the electrolyte, the mass percentage of the compound with the structure shown in formula I is 10-40%.

4. The electrolyte according to claim 1, characterized in that The mass ratio of the compound of the structure shown in formula I to the additive is 3-14.

5. The electrolyte according to claim 1, characterized in that The additive is at least one of fluoroethylene carbonate, ethylene glycol dimethyl ether, trifluorophosphate, vinylene carbonate, 1,3-propane sultone and methyl methacrylate.

6. The electrolyte according to claim 1, characterized in that The non-aqueous solvent further comprises an ester solvent, and the mass ratio of the compound with the structure represented by Formula I to the ester solvent is 0.1-1.

7. The electrolyte according to claim 6, characterized in that The ester solvent is a carbonate solvent, and the carbonate solvent includes at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl propyl carbonate, methyl ethyl carbonate, and methyl butyl carbonate.

8. The electrolyte according to claim 1, characterized in that The mass ratio of the compound of the structure represented by formula I to the lithium salt is 0.6-3.

9. A secondary battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and the electrolyte according to any one of claims 1 to 8.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.

Citation Information

Patent Citations

  • Lithium ion battery non-aqueous electrolyte solution and lithium ion battery

    CN112290089A

  • Nonaqueous electrolyte solution, nonaqueous electrolyte solution battery, and compound

    CN116711120A

  • Nonaqueous electrolyte, and use thereof

    JP2012109089A

  • Double pipe for transferring plating chemicals with joint type external pipe

    KR102412479B1

  • Secondary battery

    WO2012060445A1